Palladium-catalyzed dehydrogenative coupling of terminal alkynes with secondary phosphine oxides1. Issue 17 (28th February 2015) - Yang, Jia; Chen, Tieqiao; Zhou, Yongbo; Yin, Shuangfeng; Han, Li-Biao
<x xml:space="preserve">Abstract</x> The palladium-catalyzed dehydrogenative coupling of alkynes with secondary phosphine oxides is developed. Thus, in the presence of a silver additive, palladium acetate could efficiently catalyze the dehydrocoupling of secondary phosphine oxides with a variety of alkynes to produce the corresponding alkynylphosphine oxides in high yields. A reaction mechanism is proposed.